2021
DOI: 10.2196/24565
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention for the Transition From Pediatric or Adolescent to Adult-Oriented HIV Care: Protocol for the Development and Pilot Implementation of iTransition

Abstract: Background In the United States, adolescents and young adults are disproportionately affected by HIV and have poorer HIV-related health outcomes than adults. Health care transition (HCT) from pediatric or adolescent to adult-oriented HIV care is associated with disruptions to youths’ care retention, medication adherence, and viral suppression. However, no evidence-based interventions exist to improve HCT outcomes for youth living with HIV. Objective The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first mHealth intervention that focuses on transition readiness assessments for ALHIV. An mHealth intervention iTRANSITION, is being developed in the US to facilitate transition of youths living with HIV from pediatric to adult clinics [25]. Although, the study is being conducted in a setting with different healthcare transition models, it could potentially be adapted to other settings in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first mHealth intervention that focuses on transition readiness assessments for ALHIV. An mHealth intervention iTRANSITION, is being developed in the US to facilitate transition of youths living with HIV from pediatric to adult clinics [25]. Although, the study is being conducted in a setting with different healthcare transition models, it could potentially be adapted to other settings in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one other ongoing study is using mHealth to support the transition from pediatric to adult care for adolescents and young adults living with HIV. Specifically, Tanner et al [ 34 ] are evaluating a novel smartphone app, iTransition, based on social cognitive theory to support ALHIV in the United States. However, the development, evaluation, and implementation of effective and accessible mHealth interventions are needed to improve health care transition outcomes for adolescents living with perinatally acquired HIV in LMIC, where the majority of youth living with perinatally acquired HIV reside.…”
Section: Discussionmentioning
confidence: 99%
“…Despite studies showing poor clinical outcomes associated with healthcare transition, there is a paucity of interventions targeting this population. While our review showed that there are currently no evidence-based mHealth interventions focused on healthcare transition among youth living with HIV in LMIC, there was one protocol paper detailing a smart-phone app, iTransition, which is a Social Cognitive Theory-based mobile health intervention being developed for AYA living with HIV transitioning to adult care in the United States [ 73 ]. Additionally, a social media based mHealth intervention for AYA living with undergoing healthcare transition in South Africa, InTSHA, is currently being pilot tested [ 74 ].…”
Section: Discussionmentioning
confidence: 99%